The "Silent Scream" of "Pathetic Seeds": exploring a feminist ethics of care as a means to broaden the scope of current GM crop risk assessment practices in South Africa - Whittingham, Jennifer (Department of Environmental and Geographical Science, 2019)
The risk assessment of genetically modified (GM) crops is assumed to be a benign regulatory tool, due to its perceived objectivity and freedom from the morals and values that pervade society. Yet, against the backdrop of growing environmental pressures, social tensions and political instability, problems that cannot be accommodated in the current regulatory framework in South Africa are consistently emerging. This calls for a reformation of regulatory procedures to account for problems neglected by the current science-based risk approach to the assessment of GM crops. To achieve this, the research methodologies adopt a feminist- pragmatist approach that allows for the use of mixed methods and emphasises reflexivity to allow new perspectives to appear. The research aims to (1) study current risk assessment procedures for GM crops and their historical evolution; (2) address concerns that have arisen from this approach; and (3) investigate the suitability of a Feminist Ethics of Care as an alternative lens through which to view the assessment of GM crops in South Africa. Using themes derived from feminist literature such as relationships, particularity and context, power and vulnerability, narrative and voice, emotions and new conceptualisations of the public/private dichotomy, new 'ways of seeing’ risk emerge and illuminate salient issues that are so often neglected by the current science-based risk approach. An articulation of this alternative is explored in order to provide critical and practical policy recommendations. The thesis concludes by expressing the limitations of a Feminist Ethics of Care in the context of South Africa and reveals how a postdevelopment paradigm may help to formulate a more appropriate framework for GM crop assessment.